Analisis Sistem Antrian Pada Bank Mandiri Kantor Cabang Mulawarman Samarinda - Sarwo Eddy Wibowo 3, Muhammad Irpan 1, Elfreda Aplonia Lau 2 (EKONOMIA, 2021)
This study aims to determine the queue characteristics of Bank Mandiri Samarinda Branch Office, the effectiveness of the service on the queuing system at Bank Mandiri Mulawarman Samarinda Branch Office and to determine the amount of facility costs incurred by Bank Mandiri Mulawarman Samarinda Branch Office. In the queue structure of Bank Mandiri's Mulawarman Samarinda Branch Office, there are 3 service lines that serve cash deposits and withdrawals. Bank Mandiri Mulawarman Samarinda Branch Office uses a single-phase multi-channel service structure.The population in this study were all customers who made transactions at Bank Mandiri Samarinda Mulawarman Branch with an unlimited sample. Field observations were carried out for 5 days. The variables used in this study are the level of customer service, customer arrival rate, service facilities.The results of data analysis show that the queuing system of the Bank Mandiri Mulawarman Branch Office using a single phase multi channel 2 active teller structure is more efficient than using a single phase multi channel 3 active teller structure